Faktor-faktor yang Mempengaruhi Strategi Guru Pendidikan Agama Islam dalam Menanamkan Nila-nilai Multikultural di SMP Negeri 2 Sentan - Fatima Madjid; Umkabu, Talabudin; Muhyidin, Syaiful; Muhamad Yusuf; Zulihi, Zulihi (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Various factors can affect the success in instilling multicultural values at SMP Negeri 2 Sentani so that it can affect the PAI Teacher's strategy in instilling multicultural values in students. The purpose of this study is to comprehensively describe the factors that influence the PAI Teacher's strategy in Instilling Multicultural Values at SMP Negeri 2 Sentani. The research conducted is qualitative research using social phenomenology paradigm. Data collection techniques used passive participatory observation, in dept interviews, and documentation. Data analysis techniques used the flow model of Miles & Huberman. The results showed: The cultivation of multicultural values in schools requires the support of all parties, including teachers, parents, and the community. PAI teachers play an important role in shaping tolerance attitudes through inclusive education and based on Pancasila values. At SMP Negeri 2 Sentani, multicultural education increases tolerance, although it is still faced with challenges such as differences in identity, the influence of radicalism that is spreading among the community, and low student motivation. In Papua, the multicultural approach should respect local culture and encourage interaction across identities as a force of unity.